Leadership attributes and style of an iron lady in security industry - Saad, Natrah; Amran, Noor Afza; Abdullah, Zarifah; Ibrahim, Marhaiza (Institute for Management and Business Research (IMBRe), Universiti Utara Malaysia, 2016)
This leadership case study on Datuk Dr. Maznah Hamid, Chairman of Securiforce Group, outlines the leadership attributes and style of an iron lady of Malaysia. The case begins with a brief overview on the involvement of women business leaders in Malaysia. This is followed by a review of leadership attributes and leadership styles. Next, the study focused on Datuk Maznah’s childhood years, the initial years of her career, and how she went to become one of the prominent women business leaders in Malaysia. In that process, her leadership attributes and style are unveiled. Semi-structured interviews were conducted with Datuk Dr. Maznah herself and her three managerial employees. Gathered data were transcribed and analysed using thematic analysis. Among others, results indicated that Datuk Dr. Maznah is a visionary, determined, having integrity, and ambitious leader. She is described as a transformational leader who has the ability to inspire people with higher ideals and moral values.